Acute Limb Ischemia in Pediatric Population Secondary to Peripheral Vascular Cannulation: Literature Review and Recommendations. (July 2015) - Sadat, Umar; Hayes, Paul D.; Varty, Kevin
Introduction: In this article, we discuss published literature on the management of pediatric patients with acute limb ischemia and also present our center's experience. Results: Literature review suggests that in the absence of imminent risk of limb loss, noninterventional management with anticoagulants and systemic thrombolysis is preferable and associated with better clinical outcomes than surgery such as reduced per operative morbidity and mortality. In selected more severe cases, surgery may be required. We propose an algorithm for improved clinical outcomes based on the published literature and the American College of Chest Physicians' recommendations for antithrombotic management in the pediatric population. Conclusion: Literature review suggests an inverse relationship between age and surgical success, particularly in preschool pediatric population. Conservative management as a preliminary strategy seems most beneficial. It is hoped that the proposed intercalated algorithm of medical and surgical management of these patients can further improve clinical outcomes.